Efficiency and regulation tests of general electric transformer, type H, #497204 - Forsberg, Carl F.; Perrine, Arthur A.; McLean, Harry G. (My University, 1908)
Introduction: The static transformer is a device used for changing the voltage and current relations of an alternating current. It consists, essentially, of a pair of mutually inductive circuits called the primary and secondary coils, and a magnetic circuit interlinked with both coils. This magnetic circuit is called the core of the transformer
Citation: Forsberg, Carl F., Perrine, Arthur A., and McLean, Harry G. Efficiency and regulation tests of general electric transformer, type H, #497204. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Transformers; Electricity; Engineering; Graduating theses; Senior theses; Theses